Smart Ideas for Engineers – The Impact of Emerging Technologies on Modern Engineering Education - Axel Zafoschnig (Высшее образование в России)
Never has the speed of development in the area of engineering been as high and accelerated as it is today when we observe the enormous and driven growth of the engineering sector worldwide. These tendencies require well-coordinated new efforts in engineering education. The importance of pedagogy in the field of engineering in both the secondary and tertiary sector is growing enormously. These changes strongly demand new didactic and pedagogic paradigms. Thus, engineering education institutions across the world need to contribute relevant concepts and pedagogical ideas that can foster the development of engineering education. At the same time, the methodological and organisational challenges in engineering education need to be tackled successfully in the nearest future because collaboration, multimedia communication and complex problem solving will play an increasingly important role. This paper discusses current experiences and examines best-practice solutions, which contribute to the development of new approaches in engineering education as a multi-disciplinary field.